Perceived antidepressant efficacy associated with reduced negative and enhanced neutral mnemonic discrimination - Phillips, Taylor O.; Castro, Madelyn; Vas, Rishi K.; Ferguson, Lorena A.; Harikumar, Amritha; Leal, Stephanie L. (Frontiers in Human Neuroscience, 2023)
While antidepressants are one of the first-line treatments for depression, the mechanisms underlying antidepressant action are unclear. Furthermore, the extent to which antidepressants impact emotional and cognitive dysfunction in depression requires more fine-grained approaches toward measuring these impacts in humans. Depression is associated with emotion and mood dysregulation in addition to cognitive deficits. Depressed individuals experience general memory impairment as well as a negativity bias in episodic memory, where negative events are better remembered than positive or neutral events. One potential mechanism hypothesized to underlie the negativity bias in memory is dysfunctional hippocampal pattern separation, in which depressed individuals tend to show impaired general pattern separation but enhanced negative pattern separation. Mnemonic discrimination tasks have been designed to tax hippocampal pattern separation in humans and provide a powerful approach to develop a mechanistic account for cognitive dysfunction in depression. While antidepressants have been examined primarily in rodent models in the context of hippocampal pattern separation, this has yet to be examined in humans. Here, we investigated how antidepressant usage and their perceived efficacy was associated with emotional mnemonic discrimination, given our prior work indicating a negativity bias for mnemonic discrimination in individuals with greater depressive symptoms. We found that individuals who reported a greater improvement in their depressive symptoms after taking antidepressants (responders) showed reduced negative and enhanced neutral mnemonic discrimination compared to those with little to no improvement (non-responders). Perceived antidepressant efficacy was the strongest predictor of a reduction in the negativity bias for mnemonic discrimination, even when controlling for current depressive symptoms, antidepressant type, and other relevant factors. These results suggest that antidepressants, when effective, can shift memory dynamics toward healthy function.